2009
DOI: 10.1111/j.1463-1318.2008.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler‐guided haemorrhoidal artery ligation: long‐term outcome and patient satisfaction

Abstract: Objective Conventional Milligan-Morgan haemorrhoidectomy is associated with significant pain and potentially hazardous complications. Doppler-Guided Haemorrhoidal Artery Ligation (DGHAL) may offer a lower risk, pain-free alternative. We present our early and longterm outcome experience with DGHAL, combined with patient views and satisfaction with the procedure.Method One hundred and thirteen DGHALs were performed over a 13 month period by two surgeons in a single centre. Patients graded the severity of postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 18 publications
3
25
1
3
Order By: Relevance
“…5 However, it should be noted that the recurrence rate among the constituent studies varied considerably and ranged up to 60%. 64 Similarly, reported recurrence rates for RBL also vary widely in the literature, ranging from 11% to > 50%. [6][7][8][9][10][11] This range can be attributed to many factors, but the most pertinent is probably the difficulty in defining exactly what constitutes recurrence.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, it should be noted that the recurrence rate among the constituent studies varied considerably and ranged up to 60%. 64 Similarly, reported recurrence rates for RBL also vary widely in the literature, ranging from 11% to > 50%. [6][7][8][9][10][11] This range can be attributed to many factors, but the most pertinent is probably the difficulty in defining exactly what constitutes recurrence.…”
Section: Main Findingsmentioning
confidence: 99%
“…[6][7][8][9][10][11] This range can be attributed to many factors, but the most pertinent is probably the difficulty in defining exactly what constitutes recurrence. Some studies rely on clinical examination and patient-reported symptoms, 22,25,27,51,64 whereas others rely solely on symptomatology. 24,32 When considering symptoms only, some investigators consider a patient to be recurrence free when they have no perianal symptoms at all, whereas others consider this simply an improvement.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 DGHAL uses a Doppler probe to locate the terminal branches of the haemorrhoidal artery, then a suture is used to ligate these at multiple locations. Symptom resolution has been reported in around 85% of patients, 28 and the procedure seems to be less painful than traditional haemorrhoidectomy.…”
Section: Benign Anorectal Disordersmentioning
confidence: 99%
“…Наиболее часто применяются следующие мало-инвазивные методы лечения геморроя [1,7,18]: скле-розирование геморроидальных узлов; лигирование внутренних геморроидальных узлов латексными кольцами; инфракрасная коагуляция и электрокоа-гуляция; ультразвуковая кавитация со склерозирова-нием; дезартеризация внутренних геморроидальных узлов под контролем доплерометрии с лифтингом и мукопексией слизистой.…”
unclassified